(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: The aim of this research to try to determine the type of expected relationship between inflation as the explanatory variable and market performance as a dependent variable, for that used data issued and published by the Central Bank of Iraq and the Iraqi Stock Exchange for a sample consisting of (159) observations using the intentional or intentional sampling method for the period extending between the months (January 2010 to March 2023), in the light of each of the Consumer Price Index (CPI), the Iraqi Stock Exchange Index, the number of traded shares and the number of market capital shares to extract the market turnover rate during the research period, after that the effect between the variables was tested according to the type of relationship stipulated in This study analysed it statistically, which confirmed the effect of inflation on the market index as well as the rate of market turnover, which means that the market performance varies to the extent of the limits of interpretation of variation and in the direct positive direction of the studied variables.